English Teachers’ Acceptance of Artificial Intelligence in SMP Negeri 4 Singaraja: A Phenomenological Study - Lusiani, Andi; Indrayani, Luh; Kusuma, I Putu Indra (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
The implementation of AI in schools remains inconsistent, with many teachers showing awareness but limited classroom application. This study aims to explore English teachers’ acceptance of AI at SMP Negeri 4 Singaraja by applying the Technology Acceptance Model (TAM), focusing on the constructs of perceived usefulness and perceived ease of use. Using a qualitative phenomenological approach, data were collected through semi-structured interviews, observations, and researcher field notes involving four English teachers representing both Digital Native and Digital Transmigrant generations. Thematic analysis revealed that teachers perceive AI as beneficial for lesson preparation, assessment design, and instructional efficiency, with Digital Natives demonstrating greater fluency and confidence compared to Digital Transmigrants, who required more training and institutional support. Despite infrastructural limitations, teachers exhibited positive attitudes and strong intentions to integrate AI, viewing it as a pedagogical partner rather than a replacement for educators. In this study, teachers’ acceptance of AI is primarily shaped by its perceived usefulness, ease of use, and institutional support, suggesting that ongoing professional training and adequate facilities are vital to sustain effective AI integration in future English education